Blind recognition of LDPC code parameters over erroneous channel conditions - Ramabadran, Swaminathan (2020)
Blind reconstruction of channel coding parameters plays a significant role in non-cooperative military and spectrum surveillance applications. Further, it also gives additional advantages in applications such as cognitive radio, adaptive modulation and coding, and so on. In this study, blind estimation algorithms are proposed to identify code dimension and codeword length parameters of low-density parity-check (LDPC) codes at the receiver over noisy or erroneous channel conditions assuming a non-cooperative scenario. The proposed algorithms are validated using different test cases. Moreover, the accuracy of estimation of code dimension and codeword length parameters of LDPC codes using the proposed algorithms is also given for different M -ary phase-shift keying schemes. From the simulation results, it is observed that the accuracy of estimation improves with decrease in code rate, codeword length, and modulation order.